The Prevention of Positioning Injuries during Gynecologic Operations. Guideline of DGGG (S1-Level, AWMF Registry No. 015/077, February 2015) - Fleisch, M. C.; Bremerich, D.; Schulte-Mattler, W.; Tannen, A.; Teichmann, A. T.; Bader, W.; Balzer, K.; Renner, Stefan; Roemer, T.; Roth, S.; Schuetz, F.; Thill, M.; et al. (Geburtshilfe und Frauenheilkunde, 2015)
Purpose: Official guideline published and coordinated by the German Society of Gynecology and Obstetrics (DGGG). Positioning injuries after lengthy gynecological procedures are rare, but the associated complications can be potentially serious for patients. Moreover, such injuries often lead to claims of malpractice and negligence requiring detailed medical investigation. To date, there are no binding evidence-based recommendations for the prevention of such injuries. Methods: This S1-guideline is the work of an interdisciplinary group of experts from a range of different professions who were commissioned by DGGG to carry out a systematic literature search of positioning injuries. Members of the participating scientific societies develop a consensus in an informal procedure. Afterwards the directorate of the scientific society approves the consensus. The recommendations cover.
EVALuna2:17633